PENGACUAN DALAM WACANA TULIS DI FACEBOOK - Eulis Anggia Budiarti (Jurnal Semantik, 2012)
This research includes qualitative research on the types of written discourse on facebook regarding the use of marker variation reference cohesion. The method used is the method intended by agih Sudaryanto (1993: 15), to analyze and interpret text using the theory of discourse analysis as Teun van Dijk microstruktur basis at the level of reference. Techniques of data analysis techniques used in the form disappeared, engineering change, read markup techniques. From the results of discourse analysis in the type and form reference bookmarks. Reference marker types based on where it comes endofora reference, while according to the type includes (1) reference first persona, a persona the second, and third person, (2) reference demonstrative public bookmarks, bookmark the pronouns, pronouns bookmark affairs, and the clock, and ( 3) reference comparative ekuatif level, the level of comparative, and superlative level. Being reference marker contained in the written discourse found in the facebook include saya, aku, -ku, gue, kita,  kamu, anda, kau-, -mu, sampean, ente, you, antum, dia, -nya, mereka, ini, itu, sini, situ, begini, begitu, saat ini, hari ini, kaya, macam, seperti, lebih…, kurang…., paling, dan semakin.